PRINCIPLES OF CREATION OF PERMANENTLY WORKING SATELLITE STATE GEODESIC NETWORKS (CORS) POINTS OF UZBEKISTAN - Suyunov A. S.; Urokov O. A.; Mirzayev A. A.; Berdikulov U. (European Science Publishing, 2024)
In the article, the determination of the coordinates of the triangulation points and the errors in them were studied through the state satellite networks that work continuously in Uzbekistan. In the course of field research, based on the materials of the authors' research work in the Samarkand region, the error in determining the coordinates and distances by satellite methods was studied when the satellite moved away from the station. Building a network of GNSS stations is a new technology based on the use of satellite tools to increase geodetic accuracy.
Keywords: GPS/GNSS receiver, reference station, permanent satellite state geodetic network, CORS station, reference geodetic network, geodetic points, differential method.